The Correlation Between Low Serum T3 Levels and All-Cause and Cardiovascular Mortality in Peritoneal Dialysis Patients - Xu LC; Zhou FF; Li M; Dai ZW; Cai KD; Zhu BX; Luo Q (Dove Medical Press, 2021)
Ling-Cang Xu,1,2 Fang-Fang Zhou,1,2 Meng Li,1,2 Zhi-Wei Dai,1,2 Ke-Dan Cai,1,2 Bei-Xia Zhu,1,2 Qun Luo1,2 1Department of Nephrology, Hwa Mei Hospital, University of Chinese Academy of Sciences, Ningbo, Zhejiang Province, 315010, People's Republic of China; 2Ningbo Institute of Life and Health Industry, University of Chinese Academy of Sciences, Ningbo, Zhejiang Province, 315010, People's Republic of ChinaCorrespondence: Qun LuoDepartment of Nephrology, Hwa Mei Hospital, University of Chinese Academy of Sciences, No. 41, Northwest Street, Ningbo, Zhejiang Province, 315010, People's Republic of ChinaTel/Fax +86-574-83870217Email nbeyluoqun@126.com; luoqun@ucas.ac.cnObjective: This study is to investigate the correlation between serum triiodothyronine (T3) levels and all-cause and cardiovascular mortality in PD patients.Methods: A total of 376 end-stage renal disease (ESRD) patients who started maintenance PD treatment in the Department of Nephrology in our hospital and stable treatment for ≥ 3 months were selected, and the total T3 (TT3) and free T3 (FT3) levels were determined. Among them, 168 cases with FT3 < 3.5 pmol/L and/or TT3 < 0.92 nmol/L were divided into the low serum T3 level group, and the remaining 208 cases were divided into normal serum T3 level group. The Cox survival analysis method was used to analyze the correlation between low serum T3 levels and all-cause and cardiovascular mortality in PD patient.Results: Compared with the normal serum T3 level group, patients with low serum T3 levels had higher systolic blood pressure and a higher proportion of heart disease, and lower levels of total T4, free T4, hemoglobin, serum albumin, blood calcium, serum total bilirubin, alanine aminotransferase, and 24-h urine volume (all P < 0.05). Binary Logistic regression analysis showed that heart disease (P = 0.003, OR: 2.628, 95% CI: 1.382- 4.997) and high TT4 level (P < 0.001, OR: 0.968, 95% CI: 0.956- 0.979) were related to low serum T3 levels in PD patients. Multivariate Cox regression analysis showed that low serum FT3 level was an independent risk factor for all-cause death in PD patients (HR = 0.633, 95% CI = 0.431- 0.930; P < 0.020).Conclusion: Low serum T3 levels in PD patients were associated with heart disease and TT4 levels. Low serum FT3 levels were associated with the risk of all-cause death in PD patients.Keywords: serum T3 level, peritoneal dialysis, all-cause death, cardiovascular death, correlation